The Spectrum Analysis of Rainfall in Indonesia - Sinta Berliana Sipayung; Hariadi T.E; Nurzaman A; Eddy Hermawan (Indonesian Journal of Physics, 2003)
As a specific region at equatorial, namely maritime continent, the characteristics of meteorological element, especially rainfall in Indonesia is influenced by monsoon climate, called typical rainy and dry season. We have analyzed monthly mean of rainfall measured at twenty two (22) stations over Aceh, Medan, Padang, Jambi up to Biak for the period of 20 years (1970 to 1989). By using bandpass filter and spectrum analysis we could obtain the characteristics and predominance of Indonesian rainfall oscillation. We found that the characteristics of these rainfall could be identified in form of Semi-Annual (SAO), Quasi-Biennial Oscillation (QBO), and EL-Nino/Southern Oscillation (ENSO). We also could identify the predominance peak of these oscillations.